Ability of Gordonia alkanivorans strain 1B for high added value carotenoids production - Silva, Tiago (2016)
Currently, carotenoids are valuable bioactive molecules for several industries, such as chemical, pharmaceutical, food and cosmetics, due to their multiple benefits as natural colorants, antioxidants and vitamin precursors. Hence, the increasing interest on these high added-value products has led to the search of alternatives, more cost-effective and with better yields, towards their industrial production. Indeed, microbial metabolism offers a promising option for carotenoids production. Herein it is shown the potential of the dibenzothiophene desulfurizing bacterium Gordonia alkanivorans strain 1B as a high carotenoid-producer microorganism. The novel carotenoids, produced under different culture conditions, were extracted with DMSO and then further analyzed both through spectrophotometry and HPLC. When grown in glucose-sulfate-light, strain 1B was able of achieving 2015 g carotenoids per g DCW in shake-flask assays, with about 60% corresponding to lutein, canthaxanthin and astaxanthin. Further optimization studies open a new focus of research aiming to get a hyper pigment-producer strain that may be applied towards different industrial sectors.